2017
DOI: 10.11604/pamj.2017.27.163.11072
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 augments rapamycin in expansion of alpha fetoprotein antigen specific stem-cell-like memory T cells in vitro

Abstract: IntroductionAlloreactive tumor specific T cells are important arsenals of the adaptive immune system in the fight against tumors. However, stem cell-like memory T cells (Tscm) provide the key to effective elimination of tumor cells. Methods for generating these T cell subsets already exist. However, they could be made more efficient. Further, they are expensive and unattainable to the resource poor laboratories. In this regard, we are hereby describing a novel in vitro allogeneic co-culture method for raising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Several in vitro methods for T SCM generation have been reported, but most of them generate T SCM cells from naïve T cells [47,50,55,[63][64][65][66]. We recently reported that co-culture with NOTCH ligand-expressing feeder cells converts fully activated or more differentiated memory cells into induced T SCM -like (iT SCM ) cells [67,68] (Figure 5).…”
Section: Application Of T Scm For Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro methods for T SCM generation have been reported, but most of them generate T SCM cells from naïve T cells [47,50,55,[63][64][65][66]. We recently reported that co-culture with NOTCH ligand-expressing feeder cells converts fully activated or more differentiated memory cells into induced T SCM -like (iT SCM ) cells [67,68] (Figure 5).…”
Section: Application Of T Scm For Cancer Immunotherapymentioning
confidence: 99%
“…Less-differentiated CAR-T induction was obtained by inhibiting the Akt-mTOR pathway, enhancing FOXO1 activity, and potentiating mitochondrial function [68,[71][72][73][74][75]. Additionally, IL-21 in combination with rapamycin has been reported to enhance generation of tumor antigen-specific T SCM -like cells [64], and IL-21 enhances T CM cell formation in a FAO-dependent manner [76]. We found that FOXM1 plays an important role of the induction of the FAO-dependent OXPHOS-related genes in NOTCH-induced iT SCM cells [69].…”
Section: Application Of T Scm For Cancer Immunotherapymentioning
confidence: 99%
“…These methods could generate T SCM cells in vitro, but these methods still generate T SCM cells from na€ ıve T cells ( Table 1). [16][17][18][19][20] We have established a novel two-step culture system for T SCM induction, which is constituted by a "prime" step and an "induction" step, and have named the induced-T SCM "induced-T SCM (iT SCM )" cells. 12 In this paper, we describe a detailed methodology of iT SCM generation and report optimal conditions of priming and cytokine treatment.…”
Section: Memory T Cells Have Been Classified Into Two Subpopulationsmentioning
confidence: 99%
“…The strength of TCR stimulation, cytokine effects, and signaling inhibitors were associated with T SCM generation from na€ ıve T cells and are summarized in Table 1. 11,[16][17][18][19][20][21][22][23][24][25] In our two-step culture system, T cells are first primed and expanded by strong TCR stimulation, and are then cocultured with OP9-hDLL1 cells to convert into iT SCM cells (Figure 1A). To acquire a large number of antigen-specific CD8a + T cells, we first isolated peripheral human CD8 + T cells, labeled with cell trace dye and co-cultured them with autologous Epstein-Barr virus (EBV)transformed lymphoblastoid cell lines (LCLs) for 7 days in the "prime"…”
Section: Overview Of It Scm Cell Generationmentioning
confidence: 99%
See 1 more Smart Citation